2016
DOI: 10.1080/00016489.2016.1247985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment outcomes for benign paroxysmal positional vertigo comorbid with hypertension

Abstract: There were no significant differences in age, sex ratio, or the affected side between the h-BPPV and i-BPPV groups. The proportion of patients reporting an initial episode of positional vertigo was significantly lower in the h-BPPV group (51.22% vs 74.47%; p = .024). Patients in the h-BPPV group reported a longer median episode duration than did those in the i-BPPV group (60 days vs 15 days; p = .017). The results of treatment using repositioning maneuvers were similar between the two groups. At follow-up, 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
2
21
0
2
Order By: Relevance
“…Although the efficacy of first time CRM was significantly affected by psychiatric symptoms (Tables 2 and 3 ), the total cumulative success rate at 1 month was 97.64%, which is slightly higher than the previously reported range of 70–95% ( 54 , 55 ). Comorbidities, such as hypertension and diabetes, had no significant effect on the treatment outcome of CRM, again consistent with previous findings ( 54 , 56 ). Lastly, it has been reported that BPPV patients who received higher numbers of maneuvers tended to have the greatest risk of recurrence, and the relapse largely occurs within the first few months ( 12 ).…”
Section: Discussionmentioning
confidence: 53%
“…Although the efficacy of first time CRM was significantly affected by psychiatric symptoms (Tables 2 and 3 ), the total cumulative success rate at 1 month was 97.64%, which is slightly higher than the previously reported range of 70–95% ( 54 , 55 ). Comorbidities, such as hypertension and diabetes, had no significant effect on the treatment outcome of CRM, again consistent with previous findings ( 54 , 56 ). Lastly, it has been reported that BPPV patients who received higher numbers of maneuvers tended to have the greatest risk of recurrence, and the relapse largely occurs within the first few months ( 12 ).…”
Section: Discussionmentioning
confidence: 53%
“…Tan noted that 9% of elderly patients undergoing general geriatric assessment exhibited unrecognized BPPV (39). This percentage proved even higher in a larger series of patientsapproximately 34% (40).…”
Section: Discussionmentioning
confidence: 93%
“…No previous references about pBPPVsr and these variables have been reported yet. Nevertheless, if one considers the absence of spontaneous resolution and the recurrence of BPPV to be related phenomena (they can be confused in long-term BPPV), both age and hypertension have been linked to a higher risk of recurrence (Rashad, 2009; Tan et al., 2017).
Fig.
…”
Section: Discussionmentioning
confidence: 99%